2020
DOI: 10.1519/jsc.0000000000002143
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and Neuromuscular Measures of Intensity During Plyometric Jumps

Abstract: The aim of this study was to assess jumping performance and neuromuscular activity in lower limb muscles after drop jumps (DJ) from different drop heights (intensity) and during continuous jumping (fatigue), using markers such as reactive strength, jump height, mechanical power and surface electromyography (sEMG). The eccentric (EC) and concentric (CON) sEMG from the medial gastrocnemius (MG), biceps femoris (BF) and rectus (R) muscles were assessed during all tests. In a cross-sectional, randomized study, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 42 publications
4
49
0
Order By: Relevance
“…Therefore, 100 %CMJH may be the turning point for any observed biomechanical changes in the relative drop heights for DJ plyometric training intensity. These findings were similar to previous investigations from absolute drop heights that reported both rapid and powerful DJ performance increased from 35- [37] and 40-cm [38,39] and reported those as the turning point compared to greater heights. Larger drop heights may lead to decrements of DJ performances due to a reduction from the SSC, which might be a protective strategy for preventing muscle and tendon injury associated with a higher impact GRF [8,9,19].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, 100 %CMJH may be the turning point for any observed biomechanical changes in the relative drop heights for DJ plyometric training intensity. These findings were similar to previous investigations from absolute drop heights that reported both rapid and powerful DJ performance increased from 35- [37] and 40-cm [38,39] and reported those as the turning point compared to greater heights. Larger drop heights may lead to decrements of DJ performances due to a reduction from the SSC, which might be a protective strategy for preventing muscle and tendon injury associated with a higher impact GRF [8,9,19].…”
Section: Discussionsupporting
confidence: 91%
“…The DJ performance remained unchanged with incremental drop heights in the current study, which agreed with Bassa et al [40] and Bencke et al [41] but contrasted with Prieske et al [37], Andrade et al [38] and Lesinski et al [39]. Prieske et al [37] reported that both the DJH and RSI increased with drop heights from 20-to 50-cm and from 20-to 35-cm, respectively, in 239 adolescent handball players, irrespective of sex.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Athletes from the OPT group performed maximal-effort vertical-oriented drop jumps from an individualized box height to allow the achievement of optimal reactive strength. Individualization of box heights for the athletes in the OPT group was according to protocols previously described (3,22). Briefly, all athletes were asked to perform a maximal-effort vertical-oriented drop jump from fixed box heights of 10-cm, 20-cm, 30-cm, 40-cm, and 50-cm.…”
Section: Training Programmentioning
confidence: 99%
“…However, although power output and reactive strength index (RSI) may augment with initial increases in drop height, if height continues to increase the jump performance may be impaired (22). Moreover, increasing the drop height during drop jumps does not ensure greater electromyographic responses in all targeted muscle groups (3). Thus, the use of "optimal drop heights" based on the highest RSI values have been suggested as a simple and effective way to prescribe plyometric training routines (22).…”
Section: Introductionmentioning
confidence: 99%